A Survey of Registered Dietitians’ Concern and Actions Regarding Climate Change in the United States - Hawkins, Irana W.; Balsam, Alan L.; Goldman, Robert (Frontiers in Nutrition, 2015)
Dietary choices are a viable solution to reduce greenhouse gas emissions. While Registered Dietitians are on the front lines of food and nutrition recommendations, it is unclear how many are concerned with climate change and take action in practice in the United States. We explored concern about climate change amongst Registered Dietitians, and identified factors that may influence practice-related behaviors. Our study population included a random sample of all Registered Dietitians credentialed in the United States. Primary data was gathered using a cross-sectional survey. Of the 570 survey responses, 75% strongly agreed or agreed that climate change is an important issue while 34% strongly agreed or agreed that dietitians should play a major role in climate change mitigation strategies. Thirty-eight percent engaged in activities that promoted diet as a climate change mitigation strategy. Vegetarian (p=0.002) and vegan dietitians (p=0.007) were significantly more likely than non-vegetarian and non-vegan dietitians to engage in activities that promoted diet as a climate change mitigation strategy. Overall, concern for climate change amongst dietitians varied significantly by the region of the country in which the dietitian resided, and awareness that animal products are implicated in climate change. Registered Dietitians in the United States are concerned with climate change. However, there is a discrepancy between concern and practice-based actions. These results suggest the need for educational and experiential opportunities connecting climate change mitigation to dietetics practice.